2024
DOI: 10.1101/2024.02.22.581541
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-bound State Discovered in the Unbinding Pathway of Fluorinated Variants of the Trypsin-BPTI Complex Using Random Acceleration Molecular Dynamics Simulations

Leon Wehrhan,
Bettina G. Keller

Abstract: The serine protease trypsin forms a tightly bound inhibitor complex with Bovine Pancreatic Trypsin Inhibitor (BPTI). The complex is stabilized by the P1 residue Lys15, which interacts with the negatively charged amino acids at the bottom of the S1 pocket. Truncating the P1 residue of wildtype BPTI toα-aminobutyric acid (Abu) leaves a complex with moderate inhibitor strength, which is held in place by additional hydrogen bonds at the protein-protein interface. Fluo-rination of the Abu residue partially restores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Ye et al demonstrated in inhibition assays that fluorination of the unnatural amino acid α-butyric acid in direct proximity of a water filled binding pocket in a protein–protein complex can restore inhibitor activity. Following the hypothesis that the restoration in inhibitor strength is driven by the fluorine binding to the water network in the binding pocket, eventually establishing a water mediated bond to the protein, we investigated the water network of the complex and its interaction with the fluorinated amino acid using molecular dynamics simulations. , While we found the water molecules in the binding pocket to be highly connected and binding to the protein receptor, we did not observe any hydrogen-bond-like interactions with fluorine as acceptor.…”
Section: Resultsmentioning
confidence: 96%
“…Ye et al demonstrated in inhibition assays that fluorination of the unnatural amino acid α-butyric acid in direct proximity of a water filled binding pocket in a protein–protein complex can restore inhibitor activity. Following the hypothesis that the restoration in inhibitor strength is driven by the fluorine binding to the water network in the binding pocket, eventually establishing a water mediated bond to the protein, we investigated the water network of the complex and its interaction with the fluorinated amino acid using molecular dynamics simulations. , While we found the water molecules in the binding pocket to be highly connected and binding to the protein receptor, we did not observe any hydrogen-bond-like interactions with fluorine as acceptor.…”
Section: Resultsmentioning
confidence: 96%